Preoperative transarterial embolization for buccal region lymphangioma - Latief, Nikmatia; Rosdiana, Rosdiana; Hamdani, William; Laidding, Sachraswaty R.; Iskandar, Muslim; Santosa, Jeremy Y. (Journal of Case Reports in Dental Medicine, 2024)
Objective: These clinical findings were subsequently corroborated by anatomic pathology (PA) examination.Methods: Lymphangiomatosis, on the other hand, is a rare condition characterized by multifocal lymphatic proliferation, typically diagnosed during childhood. It affects various parenchymal organs, including the lungs, liver, spleen, bones, and skin. Lymphangiomas manifest across a wide age spectrum among patients and occur at multiple anatomical sites, presenting a diverse range of clinical and radiological manifestations.Â  The management of these tumors is complex and often requires involvement of multiple medical specialists, including orthopedic surgeons, radiologists, general surgeons, neurosurgeons, and oncologists.Results: The primary aim of presurgical embolization is to achieve devascularization of the tumor before surgical resection, resulting in reduced intraoperative blood loss and fewer complications. It is advisable to perform early resection following embolization, as revascularization can occur within six weeks in some cases.Conclusion: Limited research has been conducted on the embolization of musculoskeletal tumors for neoadjuvant, therapeutic, and palliative purposes. Nevertheless, there is a shortage of data regarding the results of presurgical embolization for musculoskeletal tumors.